The Ne Bis In Idem Principle in Tax Law: European and Italian Frameworks - Stefania Lotito Fedele (Central European Public Administration Review)
In the national and supranational legal area, the need to address the ne bis in idem principle is justified by the growing interest aroused by the most recent pronouncements of the European Courts. The principle prohibits anyone who has already been acquitted or convicted in a previous trial from being tried again. Moreover, it has become a fundamental right enshrined in the European Convention on Human Rights and the Charter of Fundamental Rights of the EU. The interest in the issue also derives from the need to understand whether the approach of the Italian legal system – or any other similar national order – can be considered compliant with European tax law and case law, based on the definitions of criminal and tax offences. Thus, talking about a European legal space means rethinking the idea of punitive power in a dimension that tends to be ‘solidarity-based’. The State can consider itself impervious to repressive demands from outside but is instead called to cooperate actively to safeguard its own guarantees. The traditional self-referential conception of criminal repression effectively summarised in the expression ‘punitive sovereignty’ gives way to an idea of jurisdiction that draws directly from the principle of mutual recognition. In this scenario, the profile of the protection of the individual from the risk of a duplication of the exercise of punitive power for the same fact in different states assumes the role of the first magnitude. Hence, there is a need to act on two levels at the same time: to seek solutions aimed at resolving possible conflicts of jurisdiction (prohibition of competing prosecutions for the same fact), and to attribute, within each Member State, preclusive effects to the previously judged foreigner (ne bis in idem).